Kartu Indonesia Pintar (KIP) Scholarship: Target Reached or Missed? - Nadya Khairani Afiefa; Masduki Ahmad (Edunesia: Jurnal Ilmiah Pendidikan, 2023)
Kartu Indonesia Pintar (KIP) scholarship is one of the scholarships that have many enthusiasts and is still a hot issue in the world of education until now. The problem arising from the scholarship is that the recipient students are considered to have a more consumptive lifestyle than regular students. This study aims to analyze whether Kartu Indonesia Pintar (KIP) scholarship is exemplary on target or needs to include the mission and purpose of the scholarship itself. Furthermore, this research is qualitative research with a descriptive approach. Data collection techniques were carried out through three instruments: observation, interviews, and documentation, called data triangulation. Interviews were conducted by questioning 5 respondents who were students who received Kartu Indonesia Pintar (KIP) scholarship. After that, the data that has been collected is analyzed to make a deeper interpretation in three stages, namely data reduction, data presentation, and conclusion drawing. Based on the results of the research that has been found, it can be concluded that the cost of education for Kartu Indonesia Pintar (KIP) is by the target, while the cost of living for Kartu Indonesia Pintar (KIP) is still deviating from its primary mission and purpose.